DETEKSI UNSUR HARA MAKRO N,P,DAN K PADA DAUN TANAMAN KELAPA SAWIT (Elaeis guineensis Jacq) DENGAN MENGGUNAKAN METODE IMAGE PROCESSING BERDASARKAN FILTER SOBEL - Zulham Effendi; Ingrid Ovie Yosephine; M.Hasby Atthariq Sembiring (Jurnal Agro Estate, 2018)
The use of leaf color chart is one way to analyze fertilizer needs. This tool is suitable to optimize the delivery of N, P, and K elements to oil palm. The use of visual technology in the form of image processing can facilitate in analyzing an object without directly related to the object being observed. The image of oil palm through image processing can be analyzed with the greenishness of the leaves so as to predict the fertility of oil palms.